Protective potential of outer membrane vesicles derived from a virulent strain of Francisella tularensis - Pavkova, Ivona; Bavlovic, Jan; Kubelkova, Klara; Stulik, Jiri; Klimentova, Jana (Frontiers in Microbiology, 2024)
Francisella tularensis secretes tubular outer membrane vesicles (OMV) that contain number of immunoreactive proteins as well as virulence factors. We have reported previously that isolated Francisella OMV enter macrophages, cumulate inside and induce strong pro-inflammatory response. In the current article we present that OMV treatment of macrophages also enhances phagocytosis of the bacteria and suppresses their intracellular replication. On the other hand, the subsequent infection with Francisella is able to revert to some extent the strong pro-inflammatory effect induced by OMV in macrophages. Being derived from the bacterial surface, isolated OMV may be considered as “non-viable mixture of Francisella antigens” and as such, they present a promising protective material. Immunization of mice with OMV isolated from virulent F. tularensis subsp. holarctica strain FSC200 prolonged the survival time but did not fully protect against the infection with lethal dose of the parent strain. However, the sera of the immunized animals revealed unambiguous cytokine and antibody response and proved to recognize a set of well-known Francisella immunoreactive proteins. For these reasons Francisella OMV present an interesting material for future protective studies.